Model Theory and Applications Lectures given at a Summer School of the Centro Internazionale Matematico Estivo (C.I.M.E.) held in Bressanone (Bolzano), Italy, June 20-28, 1975 - Mangani, P. (C.I.M.E. Summer Schools, 2011)
Lectures: G.E. Sacks: Model theory and applications.- H.J. Keisler: Constructions in model theory.- Seminars: M. Servi: SH formulas and generalized exponential.- J.A. Makowski: Topological model theory.